25 - FUNCTIONAL AUTONOMY AMONG ELDERLY PRACTICING DIFFERENT PHYSICAL EXERCISE MODALITIES (Fiep Bulletin - online, 2022)
The current public health panorama in Brazil has generated several arguments aimed at the treatment and reduction of physical and pathological changes that affect the functional capacity of elderly people, however, changes in lifestyle habits have been triggering problems such as muscle weakness, deviations postural, loss of balance, flexibility and agility. This is a field study, where the research is classified as exploratory and with a quantitative approach. Fifteen people with an average age of 68.3 ± 3.6 years participated in this study, 5 from Bodybuilding, 5 from Gymnastics and 5 from Walking. The Functional Assessment Protocol of the Latin American Development Group for Maturity (GDLAM) was used. The data obtained (IG) were analyzed and a significant improvement in all tests in the Bodybuilding modality was proven, while the other modalities were classified as weak. It was verified that the weight training modality was efficient to increase the muscular strength of the lower and upper limbs of the elderly. These data help to encourage an active style and quality of life for the elderly, in order to reduce the physical and cognitive limitations of this population.
Keywords: Functional capacity; elderly; quality of life